Caracterización epidemiológica de los ingresos hospitalarios de malaria en el Ecuador durante los años 2017 al 2021 - Quiñonez Román, Luisa Fernanda (2024)
Malaria is caused by the Plasmodium parasite transmitted by mosquitoes of the genus Anopheles. All people of different age and sex ranges can contract this disease. P. falciparum causes major complications, but the most prevalent species in the Region of the Americas is P. vivax, while P. malariae and P. ovale are less well known. The present research aimed to describe the progress of malaria cases by hospital admissions according to sex, age and etiology from the period 2017 to 2021, in addition to designing a digital strategy to promote the promotion and prevention of malaria in Ecuador. A quantitative, qualitative and cross-sectional approach was applied with a total of 843 data that were taken from the National Institute of Statistics and Census of Ecuador. They were organized in the Excel program version 2019, which was used to build the database that was exported to the SPSS program, in order to perform descriptive calculations and graphs between variables. In the results, adult males predominated, representing 63.5% and the etiological agent that caused the greatest number of admissions was P.falciparum, with a decreasing trend except for 2019 when a rebound was recorded, P.vivax was positioned as the main causative agent from 2020 and the third agent has not been specified, thus leaving P.malarie in last place. In addition, an audiovisual resource for digital dissemination that will help the promotion and prevention of malaria in Ecuador was developed. It is concluded that malaria admissions prevailed in men aged 20 to 64 years, and that the main causative agent was P.falciparum until 2019 and from 2020 P.vivax prevailed